Ambulatory pulmonary vein isolation workflow using suture-mediated vascular closure devices: a prospective observational cohort study. (19th May 2022) - Fabbricatore, D; Mileva, N; Valeriano, C; Buytaert, D; Paolisso, P; Paolisso, P; Geelen, P; Geelen, P; De Potter, T
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Cardiovascular Abbott D. Fabbricatore is supported by a research grant from the CardioPaTh PhD Program Background: Pulmonary vein isolation (PVI) for the treatment of atrial fibrillation (AF) is an increasingly performed procedure worldwide, presenting an attractive opportunity for performing it in a day care setting.[1] The main reason for delayed discharge are the potential vascular complications that may occur.[2–5] There is still a lack of knowledge considering the usage of vascular closure devices in the electrophysiological field. Purpose: The aim of the study was to evaluate feasibility, safety, and efficacy of a suture-mediated vascular closure device in ambulatory management after PVI. Methods: Prospective single-centre cohort study on 50 patients admitted for PVI from January 2020 to May 2021. At the end of the procedure, a suture-mediated vascular closure system was used for each vascular access. The feasibility of an ambulatory PVI strategy was assessed as the percentage of patients being able to be discharged the same day of the procedure. Outcomes were defined as acute rate of vascular device closure performance, postprocedural time to haemostasis, time to ambulation and time to discharge. Vascular complications, analysed on the total number of patients enrolled, were assessed during the 30-days follow-up. Results: A total of 48/50 (96%) patients were discharged at the same day of the procedure. Haemostasis was reached within 1 minute after the deployment of the device in 30 patients (60%). During the post-operative stay, two patients had minor bleeding without necessity of intervention and one patient was kept in supine position until an ultrasound evaluation resulted negative. Mean and median time to be deemed suitable for discharge in the 48 patients who reached the primary endpoint were 4:55 (±00:54) and 4:48 (2:50-7:30) hours respectively. Mean and median time to discharge were 5:48 (± 1:03) and 5:51 (3:38-7:57) hours respectively. Patient satisfaction was queried and resulted excellent. No major vascular complications were observed during 30-days follow up. Minor complications occurred in 4 patients and were three minor superficial haematomas (<6 cm) and one transient access site related nerve injury. Conclusion: The use of a closure device for femoral venous accesses after PVI led to a safe discharge of patients within 6 hours from the intervention in 96% of the population. The ambulatory management described in the abstract could be useful for minimizing the overcrowding of healthcare facilities and reduce the post-operative recovery time and management. Additionally, patients were satisfied with the treatment received. Randomised trials are needed for further evaluate the efficacy of this approach.